Potensi Rembesan Hidrokarbon Dan Pola Struktur Geologi Di Daerah Kabupaten Barru - Asri Jaya; Hasanuddin Nurdin; Ilham Alimuddin (Universitas Muslim Indonesia, 2021)
The background of this study is to provide the importance of hydrocarbon seepage information that can assist in conducting a petroleum system study, the existence of seepages on the earth's surface scattered in the Barru area has never been studied in detail. Through the analysis of geological structure analysis and hydrocarbon geochemical analysis, it has provided initial information about the presence of seepage in this region. Based on the structural pattern, the seepage position appears at the lithological contact between the Barru tectonic block and the carbonate sedimentary rock of the Tonasa Formation and is also controlled by the Northwest-Southeast (NW-SE) trending direction of structural lineament. Meanwhile, seepage in Ralla, Watu, and Ullo is controlled by the Northwest-Southeast (NW-SE) trending direction of structural lineament and is placed on the sedimentary rock of the carbonate rocks of Tonasa Formation. The results of the gas chromatography and mass spectrometry (GC-MS) determination also give different indications, namely: three locations show indications of hydrocarbon seepage with the composition of the aromatic hydrocarbons benzenediol (C8H10OS), ethanone (C7H8O3) and benzenetriol (C6H6O3), two locations are including in gas seepage which is characterized by the content of ethanol (C2H6O) and phenol (C6H6O). The presence of alkane compounds (heptadecane, octadecane, and nanodecane) indicates hydrocarbon potential in Ralla Area.